Dropout in Neural Networks Simulates the Paradoxical Effects of Deep Brain Stimulation on Memory - Tan, Shawn Zheng Kai; Du, Richard; Perucho, Jose Angelo Udal; Chopra, Shauhrat S.; Vardhanabhuti, Varut; Lim, Lee Wei (Frontiers in Aging Neuroscience, 2020)
Neuromodulation techniques such as Deep Brain Stimulation (DBS) are a promising treatment for memory-related disorders including anxiety, addiction, and dementia. However, the outcomes of such treatments appears to be somewhat paradoxical, in that these techniques can both disrupt and enhance memory even when applied to the same brain target. In this paper, we hypothesise that disruption and enhancement of memory through neuromodulation can be explained by the dropout of engram nodes. We used a convolutional neural network to classify handwritten digits and letters, and applied dropout at different stages to simulate DBS effects on engrams. We showed that dropout applied during training improved the accuracy of prediction, whereas dropout applied during testing dramatically decreased the accuracy of prediction, which mimics enhancement and disruption of memory, respectively. We further showed that transfer learning of neural networks with dropout had increased accuracy and rate of learning. Dropout during training provided a more robust “skeleton” network, and together with transfer learning, mimics the effects of chronic DBS on memory. Overall, we showed that the dropout of engram nodes is a possible mechanism by which neuromodulation techniques such as DBS can both disrupt and enhance memory, providing a unique perspective on this paradox.